2
$\begingroup$

Prove that the following formula is true for $n \geq 1$ by induction.

$a_{n} = a_{n-1} + 4n - 3 \\ a_{n} = 2n^{2} - n + 1 \\ a_{1} = 2$

My attempt follows below. I almost succeed in proving the formula for $n \geq 2$, but I fail (more specifically, I fail when I try to prove the formula for $n = k + 1$ and also, I do not know how to prove it for $n \geq 2$. Here is my attempt:

  1. Let $n = 2 \\ 2 + 2*4 - 3 = 7 (a) \\ 2*2^{2} - 2 + 1 = 7 (b) \\ (a) = (b) \space QED$

  2. Suppose the formula is true for $n = k$, which gives us: $ \\ a_{k-1} + 4k - 3 = 2k^{2} - k +1 \\$ This leads to the formula being true for $n = k + 1$: $a_{k+1-1} + 4(k+1) -3 = 2(k+1)^{2} - (k+1) + 2$

$ RHS = a_k + 4k -2 \\ LHS = 2(k^2 + 2k + 1) - k - 1 + 1 = 2k^2 +4k+2-k=(2k^2 - k +1) + 4k +1 =^{*} a_{k-1} + 4k -3 +4k+1 = a_{k-1} + 8k -2 $

From the above you see that RHS is not equal to LHS... What am I doing wrong? And when it has been shown that RHS = LHS, how does one continue to show that the formula is true not only for $n \geq 2$ but also for $n \geq 1$?

*is where I use the assumption from (2)

$\endgroup$
1
$\begingroup$

For $n=1$

$2(1)^2-1+1=2=a_1$.

Assume this holds for $k$, that is $a_k=2k^2-k+1$

Now,

$a_{n+1}=a_{n}+4(n+1)-3$

$=2n^2-n+1+4(n+1)-3$

$=2n^2+4n+2 -n$

$=2(n+1)^2-n$

$=2(n+1)^2-(n+1)+1$

The argument follows by induction.

QED.

$\endgroup$
0
$\begingroup$

I find working with $n$ is better with $k$. So: $$a_n = a_{n-1} + 4n-3=2(n-1)^2-(n-1)+1+4n-3=2n^2-4n+2-n+2+4n-3=2n^2-n+1$$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.